Identification and function analysis of drought-specific small RNAs in Gossypium hirsutum L. (March 2019) - Lu, Xuke; Yin, Zujun; Wang, Junjuan; Chen, Xiugui; Wang, Delong; Wang, Shuai; Guo, Lixue; Fan, Weili; Chen, Chao; Wang, Xiaoge; Cui, Ruifeng; Zhang, Binglei; et al.
Highlights: 379 drought-specific miRNAs could be divided into 73 miRNA families with different copy numbers. Targets Gh_A12G1620 and Gh_D01G019 improved Arabidopsis drought tolerance significantly. Small RNAs miRNA-precursors may involve in the regulation of targets methylation state. Abstract: Cotton production is severely constrained by drought, especially if encountered during the seedling stage or the fiber initiation and elongation stage, but the regulatory mechanisms underlying the effects of drought remain unclear. Therefore, characterization and functional analysis of microRNA-mediated stress regulatory networks are critical to deciphering plant drought response. In this study, 357, 379 and 377 miRNAs with annotations were obtained using the drought-resistant cotton variety ZhongH177 under three treatments, CK, drought and re-watering, and divided into 73 miRNA families with varying copy numbers from 1 to 24. 136 differential expressed genes (DEGs) with significant expression changes were found, of which only 33 DEGs were upregulated, while 103 DEGs were downregulated under drought stress. However, most DEGs recovered their initial expression states when the plants were re-watered. In total, 2657 targets were identified and found to be mainly enriched in the pathways plant-pathogen interaction, plant hormone signal transduction and biosynthesis of amino acids. Drought tolerance was significantly enhanced in 2 transgenic Arabidopsis lines, showing that miRNAs were involved in cotton drought response. Analysis of the expression patterns of 2 miRNA precursors and methylation alterations of 2 targets suggested that these miRNAs or miRNA precursors may be involved in the regulation of target methylation states. Our study provides evidence of transcriptional responses to drought stress, which will be helpful for the research of drought-resistance mechanisms in the future.